2020
DOI: 10.12669/pjms.36.6.2292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Eradication, Recurrence and Levels of 25-hydroxyvitamin D3 and Interleukin-1β in paediatric patients with Helicobacter Pylori Infection-related Gastritis

Abstract: Objective: To study whether the levels of 25-hydroxyvitamin D3 (25-(OH)D3) and Interleukin-1β (IL-1β) are correlated to the eradication and recurrence of helicobacter pylori (Hp) in paediatric patients with Hp infection-related gastritis. Methods: A total of 142 paediatric patients with Hp infection-related gastritis from November 2017 to March 2018 in Baoding Children’s Hospital were selected as study subjectswere selected as study subjects and were followed up for one year. Paediatric patients were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…6,13,14 Moreover, the genetic polymorphism of IL-1β was associated with chronic atrophic gastritis and gastric cancer, 15 and relatively higher IL-1β level may be one of the reasons for the failure of eradication in children with Hp infection. 16 Our results showed that, after triple therapy, the Hp-infected children with the failure of eradication had higher IL-1β levels than Hp-infected children with the success of eradication, which was consistent with previous reports, revealing that relatively high IL-1β level may affect the eradication effect of triple therapy.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 92%
“…6,13,14 Moreover, the genetic polymorphism of IL-1β was associated with chronic atrophic gastritis and gastric cancer, 15 and relatively higher IL-1β level may be one of the reasons for the failure of eradication in children with Hp infection. 16 Our results showed that, after triple therapy, the Hp-infected children with the failure of eradication had higher IL-1β levels than Hp-infected children with the success of eradication, which was consistent with previous reports, revealing that relatively high IL-1β level may affect the eradication effect of triple therapy.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 92%
“…Zhang et al found the lowest vitamin D serum values among a pediatric population with H. pylori recurrence, despite adequate treatment. Within their study, significantly higher values of the same parameter were found in those patients in whom bacterial eradication was successful and in healthy controls, but each of the analyzed study groups had a low percentage of vitamin D-deficient and -insufficient individuals [ 51 ]. Sorokman et al found that vitamin D levels of over 20 ng/mL are more likely to ensure eradication success.…”
Section: Resultsmentioning
confidence: 99%
“…The main population benefitting from regular vitamin D supplementation belongs to the pediatric segment. However, the limited number of pediatric studies performed on this subject did not offer any information regarding the regularity, amount, and/or adequacy of the intake of vitamin D supplements within the analyzed study populations [ 40 , 41 , 42 , 43 , 51 ]. Hence, future prospective studies and randomized controlled trials are required to clarify the relationship between vitamin D serum levels, its supplementation, and H. pylori, and to evaluate whether the addition of vitamin D3 to therapeutic regimens influences bacterial eradication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori and VitD have been suggested to be associated with gastric VitD receptors and a systemic immune response to chronic gastritis [31]. A previous study [32] showed that serum VitD levels in patients with H. pylori-associated gastritis lower. Several studies have examined the incidence of H. pylori infection in patients with varying levels of VitD [33].…”
Section: Discussionmentioning
confidence: 98%